Comparison of the Quality of Life of Type 2 Diabetes Mellitus Patients Treated with Biguanides, Thiazolidinediones and Sulphonyl ureas - Garg, Vishvas (Indian Journal of Pharmacy Practice)
Currently, more than 250 million people are suffering from diabetes mellitus (DM) worldwide. The purpose of this paper was to determine and compare the impact of the drug induced adverse drug reactions (ADRs) caused by biguanides, thiazolidinediones and sulfonylureas on the Health-Related-Quality-of-Life (HRQoL) in the T2DM patients. Using PubMed MeSH terms, comprehensive drug induced ADRs profiles of biguanides, thiazolidinediones and sulfonylureas were developed, separately. Furthermore, health utility values associated with each of the ADRs were determined using literature search. Quality-Adjusted-Life-Years (QALY's) measure was used to calculate and compare the impact of drug induced ADRs on HRQoL of the patients. Overall, we found that, followed by sulfonylureas and thiazolidinediones, metformin induced ADRs cause maximum decrement in the HRQoL of T2DM patients. We further found existence of both between group and within drug group differences between the magnitudes of the impact of different drug induced ADRs on the HRQoL of patients.
Keywords: Biguanides; Thiazolidinediones; Sulfonylureas; quality of life; adverse drug reactions; type 2 diabetes mellitus; quality-adjustedlife- years